Communicating Relative Risk Changes with Baseline Risk: Presentation Format and Numeracy Matter. (July 2014) - Bodemer, Nicolai; Meder, Björn; Gigerenzer, Gerd
Background. Treatment benefits and harms are often communicated as relative risk reductions and increases, which are frequently misunderstood by doctors and patients. One suggestion for improving understanding of such risk information is to also communicate the baseline risk. We investigated 1) whether the presentation format of the baseline risk influences understanding of relative risk changes and 2) the mediating role of people's numeracy skills.Method. We presented laypeople ( N = 1234) with a hypothetical scenario about a treatment that decreased (Experiments 1a, 2a) or increased (Experiments 1b, 2b) the risk of heart disease. Baseline risk was provided as a percentage or a frequency. In a forced-choice paradigm, the participants' task was to judge the risk in the treatment group given the relative risk reduction (or increase) and the baseline risk. Numeracy was assessed using the Lipkus 11-item scale.Results. Communicating baseline risk in a frequency format facilitated correct understanding of a treatment's benefits and harms, whereas a percentage format often impeded understanding. For example, many participants misinterpreted a relative risk reduction as referring to an absolute risk reduction. Participants with higher numeracy generally performed better than those with lower numeracy, but all participants benefitted from a frequency format. Limitations are that we used a hypothetical medical scenario and a nonrepresentative sample.Conclusions. Presenting baseline risk in a frequency format improves understanding of relative risk information, whereas a percentage format is likely to lead to misunderstandings. People's numeracy skills play an important role in correctly understanding medical information. Overall, communicating treatment benefits and harms in the form of relative risk changes remains problematic, even when the baseline risk is explicitly provided.